ANALISIS PEMBELAJARAN IPS DALAM PENDIDIKAN DI SEKOLAH DASAR: SEBUAH STUDI DI ERA SOCIETY 5.0 - I Putu Wira Adi Kusuma; I Wayan Lasmawan; I Wayan Kertih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is an important process in improving human quality, covering aspects of knowledge, skills and behavior. Social education, facilitated through Social Studies subjects in primary schools, has a crucial role in equipping students with knowledge about social and cultural life and shaping their social competencies. However, social studies learning in primary schools faces various challenges, including limited resources, teachers' lack of understanding of the material, and limited learning time. This study aims to analyze the objectives, effective methods and challenges faced in learning social studies in primary schools and provide recommendations to improve the quality of this education. The method used in this research is a literature study, by collecting and analyzing relevant academic sources. The results showed that social studies learning aims to develop social skills, understanding of the values of community life, as well as students' critical thinking skills. In addition, the use of contextual, problem-based, and technological methods, as well as increased student involvement in learning, can overcome existing challenges and improve the effectiveness of social studies learning in elementary schools.